A comparative thematic review of vocational leadership literature from the USA, Great Britain and Australia - Crossman, B.; Cameron, Roslyn (Routledge, 2014)
Vocational education and its leadership is an important sphere of economic activity worldwide and is being impacted by several trends including: the increasing significance and centrality of skills development in today’s economies; economic trends associated with globalisation (internationalisation of education and emergence of global labour markets); and demographic trends resulting in ageing populations and workforces. Leadership in vocational education contexts is crucial to the economic success of this sector. The aim of this paper is to provide a comparative thematic review of the research and literature on leadership in vocational education between the USA, Great Britain and Australia posed by the research question, ‘What are the key leadership issues facing vocational education and training sectors in the USA, Great Britain and Australia?’ This study contributes to the research and literature by identifying key impact factors for vocational education leadership in these nations over the last 13 years. Results from the comparative review established the following three key issues: a concern over equity and diversity; the importance of change management; and leadership skills and their development. Although leadership competencies are the subject of some debate there appears to be a broad consensus that leaders are developed not only by formal courses, but more importantly by on-the-job experiential learning. The future development of leaders within vocational education is discussed in relation to the implications for policy and practice, and suggestions for future research are provided.